2016
DOI: 10.1016/j.fertnstert.2016.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Effects of early cleavage patterns of human embryos on subsequent in vitro development and implantation

Abstract: Transfer of blastocysts derived from embryos that completed first and second divisions within 25.90 and 37.88 hours after culture, respectively, brings about high pregnancy rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 32 publications
1
19
0
Order By: Relevance
“…Those reports demonstrated that morphokinetic evaluation by time-lapse imaging can provide a more comprehensive and detailed analysis of the developmental events than that of static evaluation and thus may assist in selecting top quality embryos for transfer. Other studies, however, have questioned the benefit of the time-lapse system over the traditional incubators and assessment grading systems [24][25][26][27][28][29].…”
Section: % Of All Biopsy Procedures Performed In Europe Betweenmentioning
confidence: 99%
“…Those reports demonstrated that morphokinetic evaluation by time-lapse imaging can provide a more comprehensive and detailed analysis of the developmental events than that of static evaluation and thus may assist in selecting top quality embryos for transfer. Other studies, however, have questioned the benefit of the time-lapse system over the traditional incubators and assessment grading systems [24][25][26][27][28][29].…”
Section: % Of All Biopsy Procedures Performed In Europe Betweenmentioning
confidence: 99%
“…Time-lapse (TL) imaging of developing embryos offers more accurate quantification of cellular kinetics and cell cycle events than was possible with conventional static morphology assessment. A wide array of kinetic markers have been proposed to be predictive for continued embryonic development and blastocyst formation (8,(10)(11)(12)(13)(14)(15)(16). TL has also revealed the prevalence of specific dysmorphisms such as multinucleation (MU), reverse cleavage (RC), direct uneven cleavage (DUC), and irregular chaotic division (ICD) in human preimplantation embryos (10,(17)(18)(19)(20).…”
mentioning
confidence: 99%
“…When embryos show high synchrony of the first division and sufficient numbers are likely to develop into blastocysts, all the blastocysts should be cryopreserved, instead of early embryo transfer. Cryopreserved embryo transfer, which provides higher pregnancy rates, can be performed after the next cycle. In the present study, cryopreserved‐thawed blastocyst transfer achieved good pregnancy rates for all groups, suggesting that this was an effective transfer technique.…”
Section: Discussionmentioning
confidence: 99%
“…The smaller the time lag, the greater the synchrony. The study used 25.90 hours as a reference value for the definition of early‐cleavage embryos in the first division, according to the authors’ previous study . The average time of synchrony of the first division in a single oocyte retrieval cycle was 3.96 hours for 137 cycles.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation